An Analysis on Endeavours In Ict For Non-Urban Development: an Indian Viewpoint: - (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Various initiatives in the recent past portrayed thesignificant role that the I.C.Tplays in the realm of rural development. Severalprojects have reduced the costs, and it also has increased transparency. Alarge number of rural e-Governance applications, developed as pilot projectswere aimed at offering easy access to citizen services and improved processingof government to citizen transactions. This paper presents a brief review ofthe innovative projects in Information and communication technologies for ruraldevelopment and how far it has contributed. The other aim is to ponder over theachievements and the failures of ICT in the sustainable development march. Theanalysis also indicates communication related initiatives and projects fordevelopment before media liberalization and post media liberalization.